Overrreaction of The Indonesian Capital Market:Is Market Rational - Perpustakaan UGM, i-lib ([Yogyakarta] : UPT Perpustakaan UGM, 2000)
This research examines on some deviating behavior of the efficient market hypothesis and the concept of rationality. There are three main hypothesis